A method for preparing nano WC powder by using composite carbon source
Patent Information
- Application Number
- CN202610769406.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-05-31
- Filing Date
- 2026-06-01
- Publication Date
- 2026-10-09
AI Technical Summary
这种纳米WC粉末的制备方法不仅流程复杂、能耗高,而且采用高能球磨法易导致颗粒团聚和成分不均,生成缺碳相
本发明的制备方法以炭黑和可溶性有机碳源(例如葡萄糖或酚醛树脂)作为复合碳源,以紫钨(WO2.72)作为钨源,紫钨颗粒内部及表面存在大量的天然间隙为碳源的均匀分布提供了条件:复合碳源中的可溶性有机碳源溶于溶剂后携带炭黑渗透至紫钨的针棒间隙中,实现碳源在微观尺度上的均匀分布,同时渗入紫钨间隙中的碳源显著缩短了C原子的固-固扩散距离(从传统工艺的微米级缩短至纳米级),有利于提高反应效率和抑制WC晶粒长大。另一方面,复合碳源中的炭黑则确保反应体系中碳活度稳定,避免或减少了缺碳相(W2C)或游离碳的生成,有利于得到纯相结构的WC粉末。
Smart Images

Figure CN122877757A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of tungsten carbide (WC) powder preparation, specifically relating to a method for preparing nano-WC powder using a composite carbon source. Background Technology
[0002] Nano-tungsten carbide (WC) powder is a core raw material for preparing high-performance cemented carbide, cutting tools and wear-resistant coatings due to its large specific surface area, high sintering activity, high hardness and excellent wear resistance.
[0003] Chinese patent application 201810487418.8 discloses a method for preparing nano-tungsten carbide powder. This method first involves rapidly heating and cooling APT to obtain nano-tungsten trioxide, then wet-milling it with a grain growth inhibitor, followed by reduction to obtain nano-tungsten powder. The nano-tungsten powder is then mixed with carbon black and phenolic resin and subjected to high-energy ball milling before carbonization to finally obtain nano-tungsten carbide powder. This method for preparing nano-WC powder is not only complex and energy-intensive, but the high-energy ball milling method also easily leads to particle agglomeration and uneven composition, resulting in the formation of a carbon-deficient phase. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing nano-WC powder. This method uses purple tungsten as the tungsten source and utilizes a composite carbon source containing a soluble organic carbon source to fill the gaps between the purple tungsten particles, thereby achieving uniform filling of the carbon source in the purple tungsten gaps, shortening the reaction distance and reaction time, and preparing high-purity, small-particle-size, and highly uniform nano-WC powder.
[0005] The present invention provides a method for preparing nano-WC powder using a composite carbon source, wherein the composite carbon source includes a soluble organic carbon source and carbon black, and the method includes the following steps: S1, firstly, the soluble organic carbon source is uniformly dissolved in a solvent, then carbon black is added, and after being ultrasonically dispersed evenly, purple tungsten powder is added. Then, the carbon source is dispersed and stirred by ultrasonication to promote the carbon source to enter the pore structure of the purple tungsten powder, thus obtaining the precursor slurry. S2, the precursor slurry is dried to obtain precursor powder; S3, the precursor powder is placed in a tube furnace, hydrogen is introduced and the temperature is raised to 1000~1200℃, and the temperature is maintained for 1.5~3h before being cooled with the furnace to obtain nano WC powder.
[0006] In the above technical solution, the soluble organic carbon source dissolves in the solvent to form a uniform solution. Under the synergistic effect of ultrasonic dispersion and stirring, the solution containing the organic carbon source carries carbon black and penetrates into the needle-rod gaps of the purple tungsten, achieving a uniform distribution of the carbon source at the microscale. At the same time, the carbon source penetrating into the purple tungsten gaps significantly shortens the solid-solid diffusion distance of C atoms, which is beneficial to improving reaction efficiency and inhibiting grain growth.
[0007] Preferably, the average particle size of the purple tungsten powder is 10~100μm.
[0008] Preferably, the average particle size of the carbon black is 10 nm to 100 nm.
[0009] According to one specific embodiment of the present invention, the soluble organic carbon source is glucose, and the solvent is deionized water.
[0010] Preferably, by weight, the amount of carbon black is 4-16 wt% of tungsten, and the amount of glucose is 8-40 wt% of tungsten; wherein, the amount of glucose decreases as the amount of carbon black increases.
[0011] More preferably, the amount of carbon black is 4 to 10 wt% of tungsten and the amount of glucose is 25 to 40 wt% of tungsten.
[0012] According to another specific embodiment of the present invention, the soluble organic carbon source is phenolic resin, and the solvent is anhydrous ethanol.
[0013] Preferably, by weight, the amount of carbon black is 4-16 wt% of tungsten, and the amount of phenolic resin is 5-25 wt% of tungsten; wherein, the amount of phenolic resin decreases as the amount of carbon black increases.
[0014] More preferably, the amount of carbon black used is 4 to 10 wt% of tungsten, and the amount of phenolic resin used is 15 to 25 wt% of tungsten.
[0015] Preferably, in step S1, stirring is performed under heating conditions for 0.5 to 1.5 h to allow the solution to more fully penetrate the porous structure of tungsten.
[0016] Preferably, in step S3, the temperature is increased from room temperature to 1100°C at a rate of 5°C / min and held at that temperature for 2 hours.
[0017] The technical solution of the present invention has the following beneficial effects: The preparation method of this invention uses carbon black and a soluble organic carbon source (such as glucose or phenolic resin) as a composite carbon source, and tungsten oxide (WO3) as the base material. 2.72As a tungsten source, the numerous natural interstitials within and on the surface of the purple tungsten particles provide conditions for the uniform distribution of the carbon source: the soluble organic carbon source in the composite carbon source dissolves in the solvent and carries carbon black to penetrate into the needle-rod interstitials of the purple tungsten, achieving a uniform distribution of the carbon source at the microscale. Simultaneously, the carbon source penetrating into the purple tungsten interstitials significantly shortens the solid-solid diffusion distance of C atoms (from the micrometer level in traditional processes to the nanometer level), which is beneficial for improving reaction efficiency and inhibiting WC grain growth. On the other hand, the carbon black in the composite carbon source ensures stable carbon activity in the reaction system, avoiding or reducing the formation of carbon-deficient phases (W2C) or free carbon, which is beneficial for obtaining WC powder with a pure phase structure.
[0018] Furthermore, compared to phenolic resin, nano-WC powder exhibits a smaller particle size when glucose is used as the organic carbon source. This may be because glucose can better penetrate the interstitial spaces of tungsten, and glucose can undergo low-temperature pyrolysis at around 112℃ and 270℃, at which point WO3... 2.72 The pre-reduction of reducing gases that may be generated by decomposition, the uniform distribution of glucose, and the pre-reduction at low temperature work together to shorten the reduction reaction time at high temperature.
[0019] The preparation method of this invention is simple and can be industrialized at low cost. It can obtain pure phase structured nano WC powder with an average particle size of up to about 110 nm, uniform particle size distribution, and large specific surface area, providing high-quality raw materials for subsequent preparation of high-performance cemented carbide, wear-resistant coatings, etc. Attached Figure Description
[0020] Figure 1 This is a SEM image of the WC powder prepared in Example 1.
[0021] Figure 2 This is a particle size distribution diagram of the WC powder prepared in Example 1.
[0022] Figure 3 In the image: a is the XRD pattern of nano-WC powder from Example 2, and b is the XRD pattern of nano-WC powder from Example 5.
[0023] Figure 4 These are thermogravimetric analysis (TGA) graphs of samples with different carbon sources, where: a is the carbon black sample, b is the glucose sample, and c is the phenolic resin sample. Detailed Implementation
[0024] Purple tungsten (WO) 2.72As a non-stoichiometric tungsten oxide, it possesses a unique needle-like interwoven structure with numerous interstitial spaces within and on its surface, providing conditions for the uniform distribution of the carbon source. Effectively filling these interstitial spaces with the carbon source can reduce the diffusion distance of carbon atoms, increase the reaction rate, decrease the particle size of WC powder, and improve its uniformity. Based on this concept, embodiments of the present invention employ a composite carbon source containing a soluble organic carbon source, utilizing the natural interstitial structure of tungsten oxide to achieve a uniform distribution of the carbon source at the microscale, thereby improving reaction efficiency and inhibiting grain growth.
[0025] Examples 1-4
[0026] Examples 1 to 4 all used carbon black (average particle size of about 50 nm) and glucose as a composite carbon source and purple tungsten (average particle size of about 50 μm) as a tungsten source to prepare nano WC powder. The difference lies in the ratio / amount of carbon black and glucose in each example.
[0027] Specifically, the preparation method of nano WC powder in Examples 1-4 includes the following steps: S1. Add glucose to 300ml of deionized water and sonicate for 5min until completely dissolved. Then add carbon black and sonicate for another 5min. Add 10g of purple tungsten powder and sonicate for another 5min. Then place the mixed slurry in a constant temperature magnetic stirrer and stir at 90℃ and 200r / min for 1h to obtain the precursor slurry.
[0028] S2, the precursor slurry is transferred to a crucible and placed in a forced-air drying oven at 80°C for 1 hour to obtain precursor powder.
[0029] S3. The precursor powder is placed in a tube furnace, hydrogen gas is introduced (50 ml / min), and the temperature is increased to 1100℃ at a heating rate of 5℃ / min. The temperature is held for 2 hours, and the furnace is cooled to obtain nano WC powder.
[0030] The raw material ratios and average particle sizes of the nano-WC powder in Examples 1 to 4 are shown in Table 1 below. It can be seen that as the proportion of glucose in the composite carbon source increases, the average particle size of the WC powder first decreases and then increases. The nano-WC powder in Example 2 has a minimum average particle size of approximately 110 nm.
[0031] Table 1: Raw material ratios and average particle size of WC powder in Examples 1-4
[0032] Examples 5-8 Examples 5 to 8 all used carbon black (average particle size of about 50 nm) and phenolic resin as composite carbon sources and purple tungsten (average particle size of about 50 μm) as tungsten source to prepare nano WC powder. The difference lies in the different ratios / amounts of carbon black and phenolic resin in each example.
[0033] Specifically, the preparation method of nano WC powder in Examples 5-8 includes the following steps: S1. Add phenolic resin to 300 ml of anhydrous ethanol, sonicate for 5 min, add carbon black and continue sonicating for 5 min, finally add purple tungsten and sonicate for 5 min, place the mixed slurry in a constant temperature magnetic stirrer, stir at 70℃ and 250 r / min for 1 h to obtain the precursor slurry.
[0034] S2, the precursor slurry is transferred to a crucible and placed in a forced-air drying oven at 70°C for 1 hour to obtain precursor powder.
[0035] S3. The precursor powder is placed in a crucible and then placed in a tube furnace. Hydrogen gas (50 ml / min) is introduced and the temperature is increased to 1100℃ at a heating rate of 5℃ / min. The temperature is held for 2 hours and then cooled with the furnace to obtain nano WC powder.
[0036] The raw material ratios and average particle size of nano WC powder in Examples 5 to 8 are shown in Table 2 below. It can be seen that as the proportion of phenolic resin in the composite carbon source increases, the average particle size of WC powder gradually decreases.
[0037] Table 2: Raw material ratios and average particle size of WC powder in Examples 5-8
[0038] like Figure 3 As shown, XRD analysis reveals only the diffraction peaks of WC, indicating that the preparation method of the examples can obtain pure-phase WC nanoparticles. Among them, the peak intensity of sample 5 (corresponding to b in the figure) is higher, indicating better crystallinity.
[0039] Comparative Example 1
[0040] Comparative Example 1 uses carbon black as a carbon source to prepare nano-WC powder. The specific steps are as follows: First, 2.0 g of carbon black (average particle size of about 50 nm) is added to 300 ml of deionized water and sonicated for 5 min. Then, 10 g of purple tungsten powder (average particle size of about 50 μm) is added and sonicated for 5 min. Subsequently, the mixed slurry is placed in a constant temperature magnetic stirrer and stirred at 80 °C and 250 r / min for 1 h to obtain a precursor slurry. Then, the precursor is transferred to a crucible and placed in a forced-air drying oven at 80 °C for 1 h to obtain precursor powder. Finally, the precursor powder is placed in a crucible and placed in a tube furnace. Hydrogen gas is introduced (50 ml / min), and the temperature is increased to 1100 °C at a heating rate of 5 °C / min and held for 2 h. After cooling in the furnace, nano-WC powder with an average particle size of 314.46 nm is obtained.
[0041] Comparative Example 2
[0042] Comparative Example 2 uses glucose as a carbon source to prepare nano-WC powder. The specific steps are as follows: First, 4.9g of glucose is added to 300ml of deionized water and sonicated for 5min. Then, 10g of purple tungsten powder (average particle size of about 50μm) is added and sonicated for 5min. Subsequently, the mixed slurry is placed in a constant temperature magnetic stirrer and stirred at 80℃ and 250r / min for 1h to obtain a precursor slurry. Then, the precursor is transferred to a crucible and placed in a forced-air drying oven at 80℃ for 1h to obtain precursor powder. Finally, the precursor powder is placed in a crucible and placed in a tube furnace. Hydrogen gas is introduced (50ml / min), and the temperature is increased to 1100℃ at a heating rate of 5℃ / min and held for 2h. After cooling in the furnace, nano-WC powder with an average particle size of 357.01 nm is obtained.
[0043] Comparative Example 3
[0044] Comparative Example 3 uses phenolic resin as a carbon source to prepare nano-WC powder. The specific steps are as follows: First, 2.72g of phenolic resin is added to 300ml of anhydrous ethanol and sonicated for 5min. Then, 10g of purple tungsten powder (average particle size of about 50μm) is added and sonicated for 5min. Subsequently, the mixed slurry is placed in a constant temperature magnetic stirrer and stirred at 80℃ and 250r / min for 1h to obtain a precursor slurry. Then, the precursor is transferred to a crucible and placed in a forced-air drying oven at 80℃ for 1h to obtain precursor powder. Finally, the precursor powder is placed in a crucible and placed in a tube furnace. Hydrogen gas is introduced (50ml / min), and the temperature is increased to 1100℃ at a heating rate of 5℃ / min and held for 2h. After cooling in the furnace, nano-WC powder with an average particle size of 431.32 nm is obtained.
[0045] like Figure 4As shown in Figure a, when carbon black is used as the carbon source, the sample mass does not change significantly before 855℃. When the temperature rises above 855℃, the sample mass decreases rapidly, indicating that the reduction reaction begins at 855℃. When the temperature rises to 1100℃, the TG curve is still not flat, indicating that the reduction reaction is not complete. It can be seen that when carbon black is used as the carbon source, a higher temperature is required to prepare pure WC powder.
[0046] like Figure 4 As shown in Figure b, when glucose is used as the carbon source, the sample mass begins to decrease at 112℃, indicating the initial decomposition of glucose. At 270℃, the sample mass decreases at a faster rate after a brief plateau, and after 423℃, the glucose is essentially completely decomposed. The reduction reaction begins at 853℃ and ends at 978℃. Compared to carbon black, the reaction temperature range of the reduction reaction is significantly shortened, which may be due to the uniform distribution of glucose in WO3 after dissolving in water. 2.72 Between the pores, and glucose underwent concentrated decomposition between 112℃ and 423℃, at which point WO3... 2.72 The pre-reduction of reducing gases that may be generated by decomposition, the uniform distribution of glucose, and the pre-reduction at low temperature work together to shorten the reduction reaction time at high temperature.
[0047] like Figure 4 As shown in Figure c, when phenolic resin is used as the carbon source, the sample mass continuously decreases before 834℃, indicating that the pyrolysis of phenolic resin differs from the concentrated decrease in glucose within the low-temperature range; the decrease is continuous. Similarly, the reaction temperature range of the reduction reaction is also significantly shortened, starting at 834℃ and ending at 964℃. This demonstrates that glucose and phenolic resin can shorten the temperature range of the reduction reaction and accelerate the reaction rate.
[0048] When organic carbon is used alone as the carbon source, it can pyrolyze and release carbon at a relatively low temperature, which is beneficial for the early carbonization reaction. However, this also leads to the formation of local high carbon potential regions in the early stages of the reaction, causing a small number of crystal nuclei to grow rapidly, which is not conducive to further refinement of the grain size. This invention adds organic carbon to carbon black to achieve a microscale distribution of the carbon source. This allows for the suppression of WC grain growth while appropriately improving reaction efficiency and reducing reaction temperature, resulting in smaller-sized nano WC powder.
[0049] While the present invention has been disclosed above with reference to specific embodiments, it should be understood that the above specific embodiments are not intended to limit the scope of the present invention. Any person skilled in the art can make some modifications without departing from the scope of the invention; that is, all equivalent modifications made in accordance with the present invention should be covered by the protection scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the claims.
Claims
1. A method for preparing nano-WC powder using a composite carbon source, characterized in that, The composite carbon source includes a soluble organic carbon source and carbon black, and the method Includes the following steps: S1, firstly, the soluble organic carbon source is uniformly dissolved in a solvent, then carbon black is added, and after being ultrasonically dispersed evenly, purple tungsten powder is added. Then, the carbon source is dispersed and stirred by ultrasonication to promote the carbon source to enter the pore structure of the purple tungsten powder, thus obtaining the precursor slurry. S2, the precursor slurry is dried to obtain precursor powder; S3, the precursor powder is placed in a tube furnace, hydrogen is introduced and the temperature is raised to 1000~1200℃, and the temperature is maintained for 1.5~3h before being cooled with the furnace to obtain nano WC powder.
2. The method for preparing nano-WC powder using a composite carbon source according to claim 1, characterized in that: The average particle size of the purple tungsten powder is 10~100μm.
3. The method for preparing nano-WC powder using a composite carbon source according to claim 1, characterized in that: The average particle size of the carbon black is 10 nm to 100 nm.
4. The method for preparing nano-WC powder using a composite carbon source according to claim 1, characterized in that: The soluble organic carbon source is glucose, and the solvent is deionized water.
5. The method for preparing nano-WC powder using a composite carbon source according to claim 4, characterized in that: By weight, the amount of carbon black is 4 to 16 wt% of tungsten, and the amount of glucose is 8 to 40 wt% of tungsten.
6. The method for preparing nano-WC powder using a composite carbon source according to claim 4, characterized in that: By weight, the amount of carbon black is 4-10 wt% of tungsten, and the amount of glucose is 25-40 wt% of tungsten.
7. The method for preparing nano-WC powder using a composite carbon source according to claim 1, characterized in that: The soluble organic carbon source is phenolic resin, and the solvent is anhydrous ethanol.
8. The method for preparing nano-WC powder using a composite carbon source according to claim 7, characterized in that: By weight, the amount of carbon black is 4 to 16 wt% of tungsten, and the amount of phenolic resin is 5 to 25 wt% of tungsten.
9. The method for preparing nano-WC powder using a composite carbon source according to claim 8, characterized in that: By weight, the amount of carbon black is 4-10 wt% of tungsten, and the amount of phenolic resin is 15-25 wt% of tungsten.
10. The method for preparing nano-WC powder using a composite carbon source according to claim 1, characterized in that: In step S3, the temperature is increased from room temperature to 1100℃ at a rate of 5℃ / min and held for 2 hours.
Citation Information
Patent Citations
Environment-friendly nano tungsten carbide powder preparation method
CN108423684A